La construcción de un contexto interno como política universitaria: el caso de la política de diálogo en la Universidad Nacional de Colombia, 1964-1966 - García Ovalle, Milder Susana (Sociedad y Economía, 2008)
This text examines the policy of dialogue proposed and developed in the Universidad Nacional de Colombia (1964-1966) for the president José Félix Patiño, like a central component that would permit to consolidate the academic reform that was proposed for the university. The text considers the virtues of that policy, exposes the resistances that found and discuses the way like the political context, and the international context, affected its development, the same thing that the efforts done for to overcome the obstacles.